Effects of Helicobacter pylori treatment on rosacea: A single‐arm clinical trial study. Issue 9 (28th April 2017) - Saleh, Parviz; Naghavi‐Behzad, Mohammad; Herizchi, Hamdieh; Mokhtari, Fatemeh; Mirza‐Aghazadeh‐Attari, Mohammad; Piri, Reza
Abstract: Rosacea is a chronic dermatological disease. Helicobacter pylori has been discussed as one of its causative factors. In this clinical trial study, we attempted to evaluate the effect of H. pylori standard eradication protocol on the rosacea clinical course. In this single‐arm clinical trial, patients ascertained to have H. pylori infection based on serological studies were assessed to examine existence of rosacea. Patients with concurrent rosacea and H. pylori infection were included in the study and underwent standard H. pylori eradication therapy. Rosacea was evaluated using the Duluth rosacea grading score at the beginning, 2 months later and at the end of the trial (day 180). Of 872 patients positive for H. pylori, 167 patients (19.15%) manifested the clinical features of rosacea. The patients with concurrent rosacea were younger ( P < 0.001) and with a female sex predominance ( P = 0.03) when compared with rosacea‐free patients. Of 167 patients, 150 received H. pylori eradication therapy, demonstrating a 92% (138/150) cure rate. The rosacea Duluth score grading on day 0, 60 and 180 among 138 patients significantly decreased in most of the criteria except for telangiectasias ( P = 0.712), phymatous changes ( P = 0.535) and the existence of peripheral involvement ( P = 0.431). The present study concluded that H. pylori eradication leads to improvement of rosacea.